Ezra, Nehemiah and Esther - McConville J. Gordon (Edinburgh, Scotland Saint Andrew, 1985)
Includes bibliographical references
Keywords: Bible. O.T. Ezra -- commentaries; Bible O.T. Nehemiah -- commentaries; Bible. O.T. Esther -- commentaries